Design and Application of Multimedia Technology-Based Curriculum for Visual Communication Majors - Chibo Zhang; Yongli Zhao (Advances in Multimedia, 2023)
The rapid change of technology has driven the information industry to advance and develop, and the computer network technology has been greatly improved, which also promotes the artistic expression of visual communication to develop in the direction of diversification and enrichment, providing designers with more sufficient performance carriers in visual communication design. As an essential communication method and medium in modern art and design, multimedia technology assumes the role of information transmission and communication in the teaching process of visual communication design and is an important communication platform. At the same time, in order to meet the market demand for talents, visual communication professional teaching is also faced with the contemporary task of cultivating innovative talents. And multimedia technology is gradually being applied in the field of education and teaching, becoming one of the driving forces to promote the evolution of teaching methods and teaching modes. Multimedia technology, as a medium of visual symbolic communication with the times, can not only expand and extend the depth and breadth of visual communication professional teaching but also promote the improvement of teaching methods and modes. This paper proposes that, against the background of continuous technological innovation, it is very necessary to further integrate multimedia technology into the teaching of visual communication majors. This paper discusses and analyzes and studies the application of multimedia technology in the teaching of visual communication from the aspect of innovative development in the teaching of visual communication.